Rebel without a cause [videorecording (DVD)] - Ray, Nicholas, 1911-1979 (Warner Home Video, 2005)
Jim Stark, the teenage son of a well-to-do family, is overcome by loneliness, frustration and anger, which leads to violence when he seeks approval of a gang of high-school hoodlums.